Determination of Cadmium in Rice by Dispersive Liquid-Liquid Micro Extraction-Hydride Generation-Atomic Fluorescence Spectrometry - Lu, Jianping; Lu, Xiufang (Asian Journal of Chemistry, 2015)
A method of determining trace cadmium in rice by dispersive liquid-liquid micro extraction coupled with hydride generation atomic fluorescence spectrometry was established using dithizone as a chelating agent, carbon tetrachloride as a solvent and ethanol as a dispersing agent. The influences of pH of aqueous solution, dithizone concentration, ethanol volume and carbon tetrachloride volume, times of extraction and centrifugation and interferences on the determination were investigated. Under the optimum experimental conditions, a linear relationship between the fluorescence intensity and cadmium concentration range of 0.005-10 μg/L was observed. The method showed a detection limit of 0.0015 μg/L cadmium and relative standard deviation of 2.10 % when applied to sample determination. A recovery of 95.2-103 % was obtained when the method was submitted to rice analysis. This method was also validated by national certified standard rice materials GB10010 and GB10015, showing a good agreement with the certified values. The method, attributed to its simplicity, fastness, accuracy, sensitivity and environmental friendliness, showed a great potential in the cadmium determination in a real work.